Lipid Biomarkers in Alzheimer's Disease - Zarrouk, Amira; Debbabi, Meryam; Bezine, Maryem; Karym, El M.; Badreddine, Asmaa; Rouaud, Olivier; Moreau, Thibault; Cherkaoui-Malki, Mustapha; El Ayeb, Mohamed; Nasser, Boubker; Hammami, Mohamed; Lizard, Gerard (Current Alzheimer Research, 2018)
Background: There are now significant evidences that lipid metabolism is affected in numerous neurodegenerative diseases including Alzheimer’s disease. These dysfunctions lead to abnormal levels of certain lipids in the brain, cerebrospinal fluid and plasma. It is consequently of interest to establish lipid profiles in neurodegenerative diseases. This approach, which can contribute to identify lipid biomarkers of Alzheimers' disease, can also permit to identify new therapeutic targets. It was therefore of interest to focus on central and peripheral biomarkers in Alzheimer's disease. Methods: A review of the literature on 148 papers was conducted. Based on this literature, the involvement of lipids (cholesterol and oxysterols, fatty acids, phospholipids) in Alzheimer's disease has been proposed. Results: Of the 148 references cited for lipid biomarkers for Alzheimer's disease, 65 refer to cholesterol and oxysterols, 35 to fatty acids and 40 to phospholipids. Among these lipids, some of them such as 24S-hydroxyckolesterol, open up new therapeutic perspectives in gene therapy, in particular. The results on the very long-chain fatty acids suggest the potential of peroxisomal dysfunctions in Alzheimer's disease. As for the phospholipids, they could constitute interesting biomarkers for detecting the disease at the prodromal stage. Conclusion: There are now several lines of evidence that lipids play fundamental roles in the pathogenesis of AD and that some of them have a prognostic and diagnosis value. This may pave the way for the identification of new therapeutic targets, new effective drugs and / or new treatments.
Keywords: phospholipids